Turkish Validation of the Standardized Cosmesis and Health Nasal Outcomes Survey - Gode, Sercan; Ozturk, Arin; Sahin, Mustafa; Berber, Veysel; Apaydin, Fazil (Facial Plastic Surgery, 2019)
The objective of this study is to provide a valid and reliable Turkish version of the original Standardized Cosmesis and Health Nasal Outcomes Survey (SCHNOS). The SCHNOS questionnaire was translated from English to Turkish using standardized guidelines. Participants completed the questionnaire twice, with an interval of 7 to 10 days. Reliability and validity analyses were performed based on these answers. Differences between the rhinoplasty and control groups, the internal consistency of the instrument (Cronbach's alpha coefficient), and the strength of association between the two repeated measures (Pearson's correlation coefficient) were analyzed. Of the 188 included individuals (106 females, 82 males; mean age 28 ± 8.4 years), 97 were in the rhinoplasty group and 91 were in the control group. The mean total SCHNOS scores were 0.6 ± 0.4 and 29.4 ± 8.9 in the control and rhinoplasty groups, respectively, and there was a statistically significant difference in total scores between the groups (p < 0.001). The internal consistency reliability of the scale was found to be highly significant (Cronbach's alpha = 0.96, with a lower 95% confidence interval of 0.89). The test–retest correlation value was 0.95 for the total score, and each item had a strong test–retest correlation, ranging from 0.92 to 0.96. The Turkish version of the SCHNOS is a valid and reliable scale for evaluating both functional and cosmetic outcomes in Turkish-speaking patients undergoing rhinoplasty.
Keywords: rhinoplasty; aesthetics; patient-reported outcome; surveys and questionnaires